Advantages of graphical nutrition facts label: faster attention capture and improved healthiness judgement. Issue 5 (4th May 2023) - Gao, Zhibing; Li, Ziang; Zhuang, Xiangling; Ma, Guojie
Abstract: Consumers have to rely on the traditional back-of-package nutrition facts label (NFL) to obtain nutrition information in many countries. However, traditional NFLs have been criticised for their poor visualisation and low efficiency. This study redesigned back-of-package NFLs integrated with bar graphs (black or coloured) to visually indicate nutrient reference values (NRVs). Two eye movement studies were performed to evaluate the ergonomic advantages of the graphical NFLs. Our findings suggested that the newly designed NFLs led to faster and better healthiness evaluation performance. The newly designed graphical labels led to a shorter time to first fixation duration and offered a higher percentage of fixation time in the nutrient reference values region compared with that observed using traditional text labels. Nowadays, many chronic diseases are associated with poor eating habits, therefore, the importance of visualisation design to nudge healthier food choices could be paid more attention to by policymakers and food manufacturers. Practitioner summary: To improve the ergonomic design of traditional nutrition facts panel (NFL), this study assessed a newly designed graphical NFL. The results showed that graphical NFL captured consumers' attention faster and improved their healthiness judgement. Moreover, a brief nutrition education can improve consumers' attention and understanding of nutrition information.